Wickedness, Moral Responsibility, and Access to Transplantable Livers - Tonkens, Ryan (Cambridge quarterly of healthcare ethics, 2018)
Under the current conditions of scarcity of transplantable livers, difficult decisions need to be made about access. There is a growing consensus that it is morally justified to give people with ARESLD lower priority than those whose need is not self-caused. The purpose of this article is to critically examine the conditions under which such prioritization is morally justified, by challenging arguments put forth by Walter Glannon and Daniel Brudney. There are serious theoretical and practical problems with these views, which have to do with the nature and scope of the (putative) moral duty not to contribute to the competition for scarce transplantable livers, and the difficulty in determining whether people are responsible for their weakness or even wickedness of character. These problems need to be resolved if we are to be morally justified in determining access based on causal and moral responsibility for being in need.